1989
DOI: 10.1002/hed.2880110111
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of cervical scrofula

Abstract: From 1970 to 1984, 32 patients were treated for tuberculous (TB) masses, which measured 1.2-5.5 cm. The posterior triangle was involved in 19 patients, anterior triangle in 7, and more than one triangle in 6 (3 bilateral). A superficial node was excised for diagnosis. Acid-fast bacilli were identified on the smear of 18 patients. Caseation necrosis was present in 27 specimens, sarcoidosis in four, nonspecific lymphadenitis in one; all cultures grew Mycobacterium tuberculosis. A chest x-ray showed no active TB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
6
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
8
6
1
Order By: Relevance
“…Extra-pulmonary tuberculosis is known to occur in the absence of pulmonary disease in /50% of cases [6]. The rate rises to /80 Á/90% for tuberculosis of the head and neck region, which is in accordance with the finding in our series.…”
Section: Discussionsupporting
confidence: 94%
“…Extra-pulmonary tuberculosis is known to occur in the absence of pulmonary disease in /50% of cases [6]. The rate rises to /80 Á/90% for tuberculosis of the head and neck region, which is in accordance with the finding in our series.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous data, the incidence of tuberculous adenitis in our cohort was highest among women, and a positive TST was noted in 90% of cases [1][2][3]15,16,[20][21][22]29,36,[47][48][49]52,62,64,68 . TB patients without peripheral lymphadenitis in our clinic were older and had a higher male predominance, but were equally likely to have a positive TST (see Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with most series 1,2,5,16,21,22,40,48,62,80 , tuberculous lymphadenitis occurred in an insidious manner with a minority of patients having constitutional symptoms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The disease is treated with a combination of anti-tuberculous drugs for either 6 or 9 months. Most clinicians agree that anti-tuberculous chemotherapy is the definitive modality of treatment for tuberculous lymphadenitis (9). Similarly, Weiler et al (10), in their series, found that anti-tuberculous chemotherapy, with or without surgical excision of the involved cervical lymph nodes, is the treatment of choice for this disease.…”
Section: Introductionmentioning
confidence: 97%